PENINGKATAN HASIL PEMBELAJARAN PENJASKES MELALUI PENDEKATAN BERMAIN LOMPAT KANGGURU (LONGU) KELAS V SD NEGERI 011 DESA BARU KECAMATAN SIAK HULU - Eriyanto Eriyanto (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated from the learning outcomes of class V SD Negeri 011 Desa Baru Kecamatan SiakHulu which is still very low. This study aims to improve learning outcomes penjaskes. From the data analysis,there is an increase of both teacher activity, student activity, and student learning result, that is teacher activityin meeting 1 cycle I percentage is 70% (high) and at second meeting increased to 80% (high). In the secondcycle of the third meeting the value of teacher activity from 80% (high) to 90% (very high) and at the fourthmeeting increased to 95% (very high). Judging from the activity of students also experienced an increase from65% (high) to 75% (high). In cycle II the third meeting becomes 85% (very high) and at the fourth meeting itincreases to 90% (very high). Judging from the result of student learning also experience improvement, fromstudent average score on base score that is 50,25 after cycle I student average score increased to 70,5 withincrease as much 20,25 point from base score. In the second cycle of student learning outcomes also increasedas much as 15.25 points from cycle I with average student's grade of 85.75. From the data analysis there is anincrease both from teacher activity, student activity, and student learning outcomes. It was concluded that theimplementation of the strategy of playing kangaroo jump (longu) can improve the learning outcomes of class VSD Negeri 011 Desa Baru Kecamatan Siak Hulu.